Nerd também samba? O lazer dos cosplayers de Star Wars no carnaval de rua de BH - Daniela Itaborahy dos Santos (2024)
Thinking of leisure as a natural process of enjoying life challenges the operational mode of the contemporary capitalist industrial system, which often governs, sometimes in overbearing tones, even the cultural production of society, including the subject of this study: a Street Carnival Block. It demands reflection on the groups and themes that compose the researched scenario: cosplayers from Nerd culture, members of a fan club passionate about the Star Wars saga. Do these individuals, who apparently did not have the habit of attending the popular festival, reflect on leisure? Does their Nerd culture influence their choice to enjoy leisure at a Carnival Block? Sensitive to these questions, this study stems from reflections on the Lefebvrian paradigmatic triad concerning perceived, conceived, and lived space. It draws on contemporary authors such as Rey González and his analyses of senses and meanings, engaging in dialogue between social space and the individual. The objective is to understand the meaning of the presence of these individuals during the procession of the Death Star United Block, which takes place within the official program of the Carnival of the Municipal Government of Belo Horizonte, focusing on the period from February 2016 to February 2023. As a theoretical and methodological option, the research is characterized as a subjective study of descriptive nature and qualitative approach. Through the analysis of the content of semi-structured interviews conducted with 20 members of the Conselho Jedi Minas fan club who participate as cosplayers in the procession, it became evident that the conception of these social actors regarding the constitution of leisure social representations is influenced by the Cultural Industry, which stimulates the consumption of massified experiences and/or products. This representation is reinforced by the means of public administration of the event, which disseminates a new capitalist lifestyle, of which leisure is an integral part, as something that nourishes Nerd culture, which at this moment guides the experience of the interviewees. Directly linked to the mass culture factor, practitioners of this leisure activity appropriate the popular festival culture by adapting it to a format that includes Star Wars themes and transforms their experience to continue seeking achievements and emotions at elevated levels of satisfaction. The leisure experiences of these individuals in relation to carnival partially diverge from the popular character of the festival because it involves content from American culture, but they do not stray from the objectives of leisure enjoyment during carnival, which they rightfully call "carnaNerd," reinforcing their identity. The study contributes to rethinking the stigma surrounding the presence of Nerd culture at carnival, moving the group away from the exclusion frame of this festival and fueling the expectations of the field of studies seeking to understand that leisure is not restricted to specific practices or events with specific commercial objectives, but should be understood as a way to ensure that its practice is present in all aspects of people's daily lives, as it is an intrinsic need of the human experience.